1992
DOI: 10.1002/1098-108x(199201)11:1<55::aid-eat2260110108>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional counseling in bulimia nervosa

Abstract: We describe a nutritional counseling program emphasizing the importance of healthy eating behavior and the practical aspects of its implementation to counter the starve/binge/purge cycle of bulimia nervosa. We describe its rationale, its implementation, and, using a case illustration, its preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…Explore the patients emotional relationship with food, and their food fears (Williams & O'Connor, 2000) Use problem solving techniques (Whisenant & Smith, 1995;Herrin, 2003) Be on the alert for the patient who uses nutrition counselling to focus on psychological issues (Herrin, 1999) Inquire as to why specific dietary information is requested when considering the function and usefulness of the material, so that appropriate recommendations can be given, and to avoid giving patients further reason to exclude foods (Ashley & Crino, 2010) 7 Behavioural strategies: Avoid weighing between sessions (O'Connnor et al, 1988;Herrin, 1999) Develop a hierarchy of foods/eating situations that the patient has been avoiding from the least to most anxiety provoking with graded exposure to these foods (Ashley & Crino, 2010) Use self monitoring to identify links between emotions (i.e. poor self-esteem, fear of losing control) and food that can be dealt with in more depth during psychotherapy (Williams & O'Connor, 2000) For reducing binge eating Limit access to food that encourages binge eating (Laessle et al, 1991;Hsu et al, 1992;Salvy & McCargar, 2002) After an episode of binge eating return to the prescribed meal plan or the next scheduled meal or snack as soon as possible (Herrin, 1999;Salvy & McCargar, 2002) Limit the amount of food available during the meal and discard leftovers (Salvy & McCargar, 2002) Avoid missing meals or snacks (Salvy & McCargar, 2002) Avoid eating from large packets (O'Connnor et al, 1988) Teach healthy coping behaviours to regain control between situations and eating response (Laessle et al, 1991) 8 Practical and social eating skills:…”
Section: G Other Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Explore the patients emotional relationship with food, and their food fears (Williams & O'Connor, 2000) Use problem solving techniques (Whisenant & Smith, 1995;Herrin, 2003) Be on the alert for the patient who uses nutrition counselling to focus on psychological issues (Herrin, 1999) Inquire as to why specific dietary information is requested when considering the function and usefulness of the material, so that appropriate recommendations can be given, and to avoid giving patients further reason to exclude foods (Ashley & Crino, 2010) 7 Behavioural strategies: Avoid weighing between sessions (O'Connnor et al, 1988;Herrin, 1999) Develop a hierarchy of foods/eating situations that the patient has been avoiding from the least to most anxiety provoking with graded exposure to these foods (Ashley & Crino, 2010) Use self monitoring to identify links between emotions (i.e. poor self-esteem, fear of losing control) and food that can be dealt with in more depth during psychotherapy (Williams & O'Connor, 2000) For reducing binge eating Limit access to food that encourages binge eating (Laessle et al, 1991;Hsu et al, 1992;Salvy & McCargar, 2002) After an episode of binge eating return to the prescribed meal plan or the next scheduled meal or snack as soon as possible (Herrin, 1999;Salvy & McCargar, 2002) Limit the amount of food available during the meal and discard leftovers (Salvy & McCargar, 2002) Avoid missing meals or snacks (Salvy & McCargar, 2002) Avoid eating from large packets (O'Connnor et al, 1988) Teach healthy coping behaviours to regain control between situations and eating response (Laessle et al, 1991) 8 Practical and social eating skills:…”
Section: G Other Strategiesmentioning
confidence: 99%
“…Practice going to a restaurant or café , eating in a group and for special occasions (Laessle et al, 1991;Hsu et al, 1992;Kirk, 1993;Hart et al, 2008;Ashley & Crino, 2010) Provide advice on shopping, meal preparation, cooking; and the practicality of meal plans (Laessle et al, 1991;Hsu et al, 1992;Merriman, 1996;ADA, 2006;Hart et al, 2008;Cockfield & Philpot, 2009;Ashley & Crino, 2010) To help patients understand eating in its social context, and the relationship between food and culture (Ashley & Crino, 2010) 9 Appetite Regulation: Relearn/increased attention to normal hunger and satiety cues (Sunday & Halmi, 1996;Williams & O'Connor, 2000) Recalibrate appetite so it accurately reflects biological needs (Herrin, 2003) 10 Dietary rules and guidelines during inpatient treatment:…”
Section: G Other Strategiesmentioning
confidence: 99%
“…Although inconsistent with CBT for BN, the programs described by Hsu et al (1992) and Rock and Curran-Celentano (1996) seem well-suited to helping overweight or obese patients control their weight, and hence, to the treatment of BED. Indeed, the use of exchange lists and calorie counting are standard elements of comprehensive dietary/behavioral treatment programs that have been shown to be effective, at least in the short-term, in the treatment of obese patients with BED (Marcus et al, 1995;Wilson & Fairburn, 1998).…”
Section: Beyond Cbtmentioning
confidence: 99%
“…The aims of a nutritional counseling program are first, to enable the patient to understand the principles of good nutrition, her nutritional needs, and the relationship between dieting and overeating, and second, to establish and maintain a pattern of regular eating through meal planning (Hsu, Holben, West, 1992). Hsu et al (1992)submitsthatgoodnutritionalknowledge may not automatically lead to healthy eating behavior.…”
Section: Treatment Componentsmentioning
confidence: 99%
“…Hsu et al (1992)submitsthatgoodnutritionalknowledge may not automatically lead to healthy eating behavior. Therefore, it is suggested that practical aspects such as meal planning, food shopping, anddining out should be addressed.…”
Section: Treatment Componentsmentioning
confidence: 99%